Optimisation of bleaching of non-wood cellulose for cosmetics and food applications : Turning oat husks from waste to product - Leinonen, Einari (My University, 2025)
Cellulose itself is white, but in natural materials, it is tightly bound to lignin and hemicellulose. The purpose of bleaching is to break down and remove the lignin that gives colour to the cellulose, allowing cellulose to show its natural whiteness. The dark colour of lignin is due to its multiple aromatic structures and the conjugated double bonds. Over the years, cellulose bleaching has undergone significant advancements and evolution cycles in the paper industry. The goal is to remove lignin as efficiently as possible while maintaining the fibre properties of cellulose enough for the intended end products to be manufactured. The evolution of bleaching was often induced by cost and efficiency targets but lately also from environmental concerns. Cellulose is used as a filler in the food industry, where it helps modify the texture of food. However, since cellulose is not broken down in the human body, its nutritional value is negligible and as dietary fibre it helps the digestion system with many positive health effects. For food industry applications, a brown, strongly colouring cellulose is generally undesirable. Firstly, in cosmetic products, cellulose is used among other purposes as a filler to provide a thick consistency. Secondly, In September 2023, EU banned the use of plastic microbeads in commercial products. Small plastic beads were used in exfoliating face creams, but cellulose-based microparticles could serve as an alternative in this market. As in food applications, in cosmetic applications it is important that the cellulose blend seamlessly into traditionally white creams. This study investigates the optimal bleaching process for non-wood oat husk cellulose produced at CH-Bioforce’s pilot plant. Two chemicals, hypochlorite and hydrogen peroxide, are used with various reaction conditions to optimise bleaching reaction chain while maintaining adequate fibre properties. With many conditions to optimise, design of experiment software is used to lesser the number of tests. While cellulose bleaching is well-studied in the paper industry, wood as a raw material differs significantly in terms of bleaching requirements. Due to non-woods’ lower content of colour-inducing lignin, a milder bleaching approach can be applied. Experiment is done with the help of a design of experiments software to try to find the optimal bleaching approach. Small batch bleaching reactions are done with chemicals called sodium hypochlorite and hydrogen peroxide. Pulp brightness and degree of polymerisation is then measured to analyse whiteness and the length of cellulose strands. Additionally, some measurements of alpha cellulose and kappa number are made to know what happens during bleaching.
Keywords: agricultural waste stream, bleaching, cellulose, circular economy, elemental chlorine free, non-wood, oat husk